Numerical Study of Tio2-Based Nanofluids Flow in Microchannel Heat Sinks: Effect of the Reynolds Number and the Microchannel Height - Garcia-Herrera, C; Ortega-Aguilera, R; Martinez-Gutierrez, V; Vasco-Calle, D (Elsevier Ltd, 2019)
In the present work, we have studied the laminar (200 ⩽ Re ⩽ 1200) three-dimensional flow of a water-based nanofluid in rectangular microchannels of constant wide cross section (283 μm) and three different heights (800 μm, 600 μm, and 400 μm). Moreover, we analyse the concentration of dispersed TiO2 nanoparticles (<6 nm) on the thermal and hydraulic performance of heat sinks with the microchannels. The numerical analysis required the use of experimental models of the viscosity and the thermal conductivity with respect to temperature TiO2 nanoparticles concentration (1 wt% and 3 wt%). Using a code based on the finite volume method to solve the transport equations that govern the studied flows, the friction factor, the Nusselt number, the convective heat transfer coefficient, and the mean temperature of the hot wall have been determined. The results show that both the use of nanofluids and the reduction of the microchannel height favour heat transfer at low Reynolds numbers, an improvement that decreases as this parameter increases. With a nanoparticles concentration of 3 wt% and a Reynolds of 200, we found a maximum 19.66% increase of the convective heat transfer coefficient with respect to the pure base fluid. However, also at low Reynolds, the greatest increases of the skin friction coefficient were registered, reaching a maximum increase of 137.68% with respect to the pure base fluid in the case of the 1 wt% nanofluid. © 2019 Elsevier Ltd